E-Module for Narrative Texts Oriented Towards Politeness for SD/MI Student - Saifullah; Gloriani, Yusida; Maschita, Dede Endang (PT Inovasi Pratama Internasional, 2024)
This research aims to develop a politeness-oriented narrative text e-module for SD/MI students. Background to the problem of this research (1) How is the design of a politeness-oriented narrative text e-module for SD/MI students? (2) What are the results of the implementation of the politeness-oriented narrative text e-module for SD/MI students? This research uses research and development methods with the ADDIE (Analysis Design Development Implementation Evaluate) model. The steps of this research consist of needs analysis, designing teaching materials (e-module), developing teaching materials (e-module), product implementation (e-module teaching materials), and product evaluation (e-module teaching materials). Data collection in this research was by collecting data from the results of expert validation questionnaires and student assessment questionnaires. The data obtained was analyzed descriptively using a Likert scale. The results of the validation test by the material expert obtained a score of 3.1, the validation test by the media expert obtained a score of 3.4. The validation test by the Indonesian language teacher obtained a score of 3.75. The results of implementing e-module teaching materials in schools received a positive response from students with a score of 3.35. The conclusion of this research is that the language politeness-oriented narrative text e-module for SD/MI students meets the criteria for being very suitable for use as teaching material by students or teachers in Indonesian language subjects as narrative text material for grade VI SD/MI students.